Electrochromic properties of silver nanowire-embedded tungsten trioxide thin films fabricated by electrodeposition. Issue 18 (15th December 2020) - Park, Yoon-Tae; Lee, Soo-Hyoung; Lee, Ki-Tae
Abstract: One of the main drawbacks of tungsten trioxide (WO3 ) electrochromic materials is slow response time due to the low electrical conductivity of WO3 . In this work, a silver nanowire (AgNW)-embedded WO3 composite structure was designed to improve electrochromic performance. The AgNW-embedded WO3 electrochromic thin films were fabricated by an electrodeposition method. In addition to phase and morphology analyses, electrochromic performance was evaluated via an examination of transmittance modulation, response time, and coloration efficiency. The electrochromic study reveals that embedding AgNWs into the WO3 has a significant impact on electrochromic performance. Due to the presence of a percolated AgNW network with high electrical conductivity and surface roughness, the AgNW-embedded WO3 thin films exhibit faster Li-ion intercalation/de-intercalation kinetics (coloration time of 12 s and bleaching time of 2 s) and a greater coloration efficiency (45.3 cm 2 /C) with better cyclic stability than a single-layer WO3 thin film. Such results indicate AgNW-embedded WO3 electrochromic thin films as attractive for practical application of electrochromic devices in energy-saving smart windows.